English or Icelandic? A False Dichotomy in a Modern Global Society - Ólöf Ásdís Baldvinsdóttir 1967- (2011)
This essay is a discussion regarding the effects that English, as the language of globalization, has on Icelandic society, culture and language. Iceland is a small country which strongly identifies itself with the Icelandic language therefore the pressure applied to the Icelandic society to improve in English and consider it a second language may generate an uncomfortable position of having to choose between maintaining preservation of the Icelandic language or increasing proficiency in English. However, for the benefit of Iceland´s role in the modern global world and its preservation of the Icelandic language, this essay will recognize this situation as a false dichotomy. This essay will also combine summaries of recent literature on the topics of English in Iceland and Preservation of Icelandic in an attempt to suggest further simultaneous research and language planning for both of the languages.